LONGING FOR KEVIN RUDD AND HIS LEGACY IN IMPROVING AUSTRALIA-INDONESIA RELATIONS - Darmawan, Harry (Journal of Social Political Sciences, 2021)
Indonesia misses Kevin Rudd's figure. The emergence and victory of Kevin Rudd in the 2007 Australian elections seemed to be a speck of light in the improvement of bilateral relations between Australia and Indonesia at that time. He succeeded in turning Australia's foreign policy into a more humanist and Asia-centric direction. A thing that was previously very rare in the era of Prime Minister John Howard. Various policies were able to reconcile the romanticism of Garuda and the Kangaroo, which is the largest ruler in Southeast Asia and the Oceania Zone. This paper examines the dynamics of Kevin Rudd's victory in the 2007 Australian Election, as well as his golden legacy in fighting for harmonization of relations between Australia and Indonesia.